Numerical and Preliminary In Situ Investigation on Roadway Excavation Using Static Expansion Mechanical Fracturing - Yin Chen; Zijun Li; Jian Zhao; Dan Huang (Advances in Civil Engineering)
This paper introduced a new nonexplosive roadway excavation method, combining the reserved free space technology and the static expansion mechanical fracturing technology, where the former is implemented by the gasbag, while the piston splitter is for the latter. The numerical model of roadway excavation was set up via PFC3D to investigate the mechanical fracturing performance, including the single-hole fracturing and the hole network fracturing. The results show that the reasonable hole margin is about 1.0–1.5 m, and the optimal column spacing of the hole network pattern is 1.0 m, after comprehensively analyzing the fracturing performance and the splitting force evolution. Moreover, the mechanical fracturing excavation method was applied to construct a parking chamber in the Kalatongke Mine, to preliminarily verify the feasibility of the static expansion mechanical fracturing technology. The in situ investigation results indicate that the excavation footage is about 0.8 m with the piston splitter when adopting a hole margin of 1.0–1.5 m. To sum up, the preliminary field application and the numerical simulation result both support the feasibility of mechanical fracturing, and the reasonable fracturing hole margin is about 1.0 m.